2016
DOI: 10.1093/bja/aev455
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial vs general anaesthesia for total hip and total knee arthroplasty: a systematic review of comparative-effectiveness research

Abstract: Neuraxial anaesthesia for total hip or total knee arthroplasty, or both appears equally effective without increased morbidity when compared with general anaesthesia. There is limited quantitative evidence to suggest that neuraxial anaesthesia is associated with improved perioperative outcomes. Future investigations should compare intermediate and long-term outcome differences to better inform anaesthesiologists, surgeons, and patients on importance of anaesthetic selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
113
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(130 citation statements)
references
References 120 publications
3
113
1
7
Order By: Relevance
“…It is considered to be superior in reducing blood loss, tourniquet pain, and analgesia, and the decreased incidence of VTE as a result of using epidural anesthesia is considered to be one of the reasons why epidural anesthesia is chosen over general anesthesia for TKA. Recent systematic reviews and meta-analysis studies have shown that although patient outcomes support regional anesthesia over general anesthesia during hospitalization, it has not been definitely concluded that there is a causal link between a particular anesthetic method and the improvement in the postoperative outcome for TKA [17,18]. In our results, we found no differences in the incidence of VTE, compared between epidural and general anesthesia for TKA.…”
Section: Discussioncontrasting
confidence: 79%
“…It is considered to be superior in reducing blood loss, tourniquet pain, and analgesia, and the decreased incidence of VTE as a result of using epidural anesthesia is considered to be one of the reasons why epidural anesthesia is chosen over general anesthesia for TKA. Recent systematic reviews and meta-analysis studies have shown that although patient outcomes support regional anesthesia over general anesthesia during hospitalization, it has not been definitely concluded that there is a causal link between a particular anesthetic method and the improvement in the postoperative outcome for TKA [17,18]. In our results, we found no differences in the incidence of VTE, compared between epidural and general anesthesia for TKA.…”
Section: Discussioncontrasting
confidence: 79%
“…Whereas some metaanalysis demonstrated a benefit with the use of neuraxial techniques, others could not. 18,19 General anesthesia is still widely used for THA. In a recent article, Memtsoudis et al 20 demonstrated that in a sample of 124,993 patients, general anesthesia was used in 78%.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip and total knee replacement are promising management strategies which are forecasted to increase dramatically during the next 20 yr [25,26] . However, most major orthopedic surgery like THR and TKR involves large injured tissues and requires much time under general or regional anesthesia.…”
Section: Discussionmentioning
confidence: 99%